IMPLEMENTATION OF MACHINE TRANSLATION AND CAT-TOOLS INTO TRANSLATION PROCESS («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article examines the inclusion of modern technologies into translation process, particularly machine translation and CAT-tools. The paper addresses the benefits and drawbacks of the implementation of innovations and proposes possible ways to avoid negative consequences of machine intervention into translation.
Keywords: machine translation; pragramtics; communication; speech situation; post- editing; cultural differences.